Elastic Band Training Enhances Sprint Acceleration, Change of Direction, and Throwing Performance in Handball Players: A Mechanistic Systematic Review - Astawa, I.N. Putra; Sudiana, I Ketut; Wijaya, Made Agus (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
Handball performance requires short-distance acceleration, rapid change of direction, jumping ability, upper limb strength, and high-velocity throwing; however, the effectiveness of elastic band training for these sport-specific components still requires careful synthesis. This study aimed to examine the effects of elastic band training on sprint acceleration, change of direction, jump performance, upper-limb strength, and throwing-related performance in competitive handball players. A scooping review with structured narrative synthesis was conducted following PRISMA 2020 guidance. Articles published between 2016 and 2025 were searched in Scopus, PubMed, Web of Science, and Google Scholar. Of the 51 records identified, 12 studies involving approximately 359 handball players met the inclusion criteria. Most participants were youth, adolescent, or junior players. The interventions lasted 6-10 weeks and were implemented two to three sessions per week. The synthesis showed that elastic band training was generally associated with improvements in short-distance sprint acceleration, change of direction, selected jump outcomes, upper-limb strength, and throwing-related performance. Change of direction demonstrated the most consistent positive pattern, whereas jump outcomes were more variable across protocols. This review concludes that elastic band training can be considered a practical complementary modality for handball conditioning, particularly among young players. Nevertheless, the physiological and biomechanical mechanisms underlying these performance changes remain inferential and require direct confirmation through future experimental studies Keywords: Elastic Band Training; Handball; Sprint Acceleration; Change of Direction; Youth Athletes.